Pengaruh Harga Dan Varian Produk Terhadap Keputusan Pembelian Produk Sophie Martin - Mahmud; Nunuk Nur Khofifah (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
This study aims to analyze the effect of price and product variants partially andsimultaneously on purchasing decisions of Sophie Martin products at BCWidiyowati Kedungwonokerto Prambon Sidoarjo. This correlational quantitativeresearch was conducted at BC Widiyowati Kedungwonokerto Prambon Sidoarjo.Determination of the sample in this study was taken 50% of the population usingproportional random sampling, namely as many as 60 respondents. The data wascollected using a questionnaire that had been tested for validity and reliability. Thedata analysis used is multiple linear regression analysis with the help of the SPSS24.0 For Windows program. Based on the results of the analysis it can beconcluded that: there is a partially significant positive effect of price and productvariants on the purchasing decision of Sophie Martin products at BC WidiyowatiKedungwonokerto Prambon Sidoarjo, this is evidenced by the value of tcount price(11.995) > t table (2,000) and tcount value of product variants (8,740) > t table (2,000).There is a significant positive effect of price and product variants simultaneouslyon the purchasing decision of Sophie Martin products at BC WidiyowatiKedungwonokerto Prambon Sidoarjo, this is evidenced by the value of Fcount(84.939) > Ftable (3.71). That price is more dominant in influencing the purchasingdecision of Sophie Martin products at BC Widiyowati Kedungwonokerto PrambonSidoarjo, this is evidenced by the value of the price correlation coefficient (0.844)> the product variant correlation coefficient value (0.754).